Chemical Photocatalysis with 1-(N,N-Dimethylamino)pyrene - Penner, Alexander; Bätzner, Effi; Wagenknecht, Hans-Achim (Synlett, 2012)
1-(N,N-Dimethylamino)pyrene was applied as chemical photocatalyst for two different organic reactions: Both the photocatalytically driven nucleophilic addition of methanol to 1,1-diphenylethylene and the photocatalytic deprotection of N-phenylsulfonylindole gave the corresponding products in good yields and in a highly sustainable way after short irradiation with high-power LED. This concept can potentially be transferred to other photochemical reactions.
Keywords: pyrene; chromophore; electron transfer; alkene; indole